ADSORPSI DAN PELEPASAN DOXORUBICIN DARI PERMUKAAN PARTIKEL MAGNETIT/HIDROKSIAPATIT - Sri Murda Niati; Ahmad Fadli; Yelmida Aziz (Jurnal Sains dan Teknologi, 2019)
Cancer is a disease caused by poor cell growth in body tissues. One effective method of dealing with cancer cell growthis the nanomedicine or nano drug delivery approach. Biocompatible, biodegredable and non-toxic drug deliverymaterial for the body is magnetite / hydroxyapatite composite. This research uses hydrothermal method to producemagnetite / hydroxyapatite composites. Furthermore, to determine the performance of magnetite / hydroxyapatitecomposites as drug delivery through adsorption kinetics and mathematical models of doxorubicin decay on the surfaceof the composite and the value of the mass transfer coefficient. The concentration of doxorubicin used for adsorptionwas 520, 720, 920 (ppm) with a composite mass of 0.2 0.3 0.4 and 0.5 (grams) and an adsorption temperature of 30, 40,50 (0C). The doxorubicin release model in the composite layer uses PBS solution media pH 7.4 with a temperature of370C. The results obtained for doxorubicin adsorption kinetics on composite surfaces were 71.43; 55.56; 90.91 mg/gfor temperature variations of 30, 40, 50 °C with (R2) is 0.980 and % SSE by 33% and kinetics constant adsorption0.282. Decay of doxorubicin in vitro using PBS solution was obtained. The value of the mass transfer coefficientobtained increased with the increase in the mass of the magnetite/hydroxyapatite composite, for the mass of themagnetite/hydroxyapatite composite 0.2; 0.3; 0.4; and 0.5 grams (kc) values obtained were 1.1 x 10-4 g/cm2.minute, 4.4x 10-4 g/cm2.minute, 9.9 x 10-4 g/cm2.minute and 2 , 1 x 10-3 g/cm2.minute.